Narrative Barriers to Social Inclusion of TTC “Mothers” in Feminist African Novel - Onuoha, Onyekachi Peter (Pedagogika Społeczna Nova, 2025)
The feminist African novel questions social practices and exclusions based on gender and social expectations of women. Procreation is the premise for marriage in African traditional society. When there is no procreation, such a marriage is believed to be cursed, incomplete, and a source of classifications and exclusions for the woman. It takes two in traditional African society to entangle and procreate. However, when couples fail to procreate as expected by their parents, relations, and communities, pressure is mounted on the woman, and she is excluded by certain narrative discourses of her fellow women that attempt to stigmatize, classify, deprive, and exclude the TTC mother from all forms of social gatherings by her fellow women. It is against this backdrop that this paper examines the narrative barriers to social inclusion for women trying to conceive (hence TTC). This paper analyses the female images of TTC mothers constructed in feminist African novels to reveal the feminist “unexamined” thought behind the female gazing of TTC women. This study accounts for narratives and social barriers to the inclusion of TTC mothers by mirroring the society in which the novel is produced. This paper applies the concepts of “proximity” and “gaze” to examine Dike’s Dear Kelechi and Adebayo’s Stay with Me. This study submits that there are narrative choices in interpersonal discourses by “mothers” that enforce social barriers in the inclusion of TTC women in African feminists’ novels. These narrative choices by women constitute social barriers and lead to various forms of suffering and denigration for TTC women.